Views of AIDS patients regarding nursing care quality in healthcare centers affiliated to Shaheed Beheshti and Tehran Universities of Medical Sciences - Dabirian, A; Zolfaghari, H; Abed Saidi, ZH; Alavi-Majd, H (Advances in Nursing & Midwifery, 2008)
Background Today, AIDS or century plaque afflicts more than 35 million people in the world. Increased number of patients in Iran and advances in the management of the disease have led to higher survival rate. In addition, increasing number of hospital admissions and side effects of its drugs have heightened the incidence of opportunistic infections. The patients may fear from social isolation and the quality of their care may be affected by horror of contraction in nursing staff. Purpose This descriptive study was conducted to assess nursing care quality in the views of patients with AIDS at healthcare centers affiliated to Shaheed Beheshti and Tehran Universities of Medical Sciences in 2007. Methods 70 patients hospitalized at least 3 days at one of infectious wards of Tehran were selected by convenience sampling method. A questionnaire with 55 items in different domains (demographics, 11; physical, 20; psychological, 14; and communication, 10) was used for data collection. It was validated and made reliable by content and test-retest methods. Conclusion 27.9% of the subjects evaluated nursing care quality as moderate. 14.3%, 11.4% and 4.1% appraised the quality as weak, good and very good respectively. No significant relationship was found between age, sex, marital status as well as educational level and the views of patients. A positive correlation was found between hospital stay and the quality in the communication domain (r=0.333) while correlation between age and the quality in this domain was negative (r=0.304, P<0.01). Conclusion It can be concluded that nursing care given to patients was inadequate to satisfy the needs and expectations of patients with AIDS. Keywords: AIDS, Quality of nursing care, Patients’ views